2021
DOI: 10.3390/buildings12010018
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Graphite Powder on the Mechanical and Acoustic Emission Characteristics of Concrete

Abstract: In this paper, uniaxial compressive strength (UCS) test and three-point bending (TPB) test, together with an acoustic emission (AE) system, were performed to investigate the mechanical properties and AE characteristic changes of concrete with different graphite powder (GP) content. The results show that: (1) Poor adhesion and low interlocking of graphite with cement stone increase the initial defects of concrete, reducing its elastic modulus and the cyclo-hoop effect, and thus weakening the compressive strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 32 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…The relationship between D s and the porosity can be seen in Figure 5a. Many researchers confirmed that the fine pores less than 50 nm dominantly affect the shrinkage behavior of concrete [36,61,[99][100][101][102][103][104]. The V 2.5-50 nm values estimated from Table 4 are shown in Table 7.…”
Section: Fractal Dimension Of Pore Surface (D S )mentioning
confidence: 85%
“…The relationship between D s and the porosity can be seen in Figure 5a. Many researchers confirmed that the fine pores less than 50 nm dominantly affect the shrinkage behavior of concrete [36,61,[99][100][101][102][103][104]. The V 2.5-50 nm values estimated from Table 4 are shown in Table 7.…”
Section: Fractal Dimension Of Pore Surface (D S )mentioning
confidence: 85%
“…A viable solution to improve the mixture properties for a better damage resistance is to add steel or carbon fibers or conductive fillers. [ 38 ] Next, we demonstrate how a conductive filler, i.e., graphite powder, can significantly reduce the initial concrete cracking while enabling a nanogenerator‐integrated concrete system.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, with the increase of the replacement ratio of BGF, the compressive strength decreased while the compressive strength of the specimen with SGF did not change. This is because the flake shape is also weak in compression [ 45 ]. The BGF led to lower compressive strength due to the larger flake shape.…”
Section: Resultsmentioning
confidence: 99%